Fenologia, potencial produtivo e fontes de adubação no cultivo do morangueiro - Cocco, Kassia Luiza Teixeira (2014)
The overall objective of this study was to determine the phenology and yield potential of strawberry cultivars and to evaluate different sources of fertilizer pre-planting in the production of strawberry grown in low tunnels. In the first experiment, were evaluated the cultivars Camarosa, Camino Real and Albion in two agricultural years. Characterized the time of occurrence and duration of nine sub-periods of phenological stages of flowering and fruiting, as well as the time elapsed between transplantation and onset of flowering, fruit formation and start and end of the harvest. The second experiment evaluated the cultivar Camarosa, and treatments consisted of nutrient sources in pre-planting, these being Control Treatment, Topmix, Formulation Commercial NPK and NPK Formulated, performing collections of plant material each 40 days. In assessing the productivity, for both experiments, there was counting the number of fruits, weighing and measuring of greater width and length as well as measurement of the levels of soluble solids. The results were submitted to analysis of variance and means were compared by Tukey test at 5% probability. To reach the beginning of flowering, fruiting and harvesting, considering the year 2012, the cultivar Camarosa was the more precocious. For the year 2013, the cultivar Albion showed more precocity. In general, the Albion, Camarosa and Camino Real cultivars totaled approximately 44 days, 40 days and 34 days, respectively to conclude stages of flowering and fruiting. For the number of pseudofruits and plant productivity, the cultivar Camarosa showed the highest values for both years. Whereas the levels total soluble solids, it is concluded that the cultivar Albion had the highest values of º Brix, for two years evaluated. At the end of the second experiment, we obtained approximately 615 g plant-1 for the treatment Topmix, showing the greater productivity of this to the conditions of this experiment were verified. The highest values of fresh weight of pseudofruits were observed on the second epoch assessed, being that the treatments were quite similar. The number of pseudofruits was higher in the third epoch evaluated, the levels of total soluble solids (SST) did not differ between seasons, the width of pseudofruits was higher in the second and fourth epochs and the length did not differ between seasons. The Topmix treatment presented the highest averages for number of pseudofruits, SST, width and length. The nitrogen contents were higher in the first epoch and the Control Treatment had the lowest values. The phosphorus contents were higher in the NPK treatment Formulated and in first epoch. For potassium, there was no difference between treatments and foliar contents were lower in the first epoch. Foliar nitrogen and potassium were found in the sufficiency ranges, while the values of phosphorus were below the range considered as sufficient in strawberry culture.